Bioactive and degradable scaffolds of the mesoporous bioglass and poly(l-lactide) composite for bone tissue regeneration. Issue 15 (2nd March 2015) - Niu, Yunfei; Guo, Lieping; Liu, Jun; Shen, Hongxing; Su, Jiacan; An, Xiaofei; Yu, Baoqing; Wei, Jie; Shin, Jung-Woog; Guo, Han; Ji, Fang; He, Dawei
Abstract : Bioactive scaffolds of the m-BG–PLLA composite with excellent biocompatibility, degradability and osteogenesis, which could be promising implants for bone regeneration. Abstract : Bioactive scaffolds of the mesoporous bioglass (m-BG) and poly(l -lactide) (PLLA) composite were fabricated using a solvent casting-particulate leaching method. The results showed that incorporation of the m-BG into PLLA significantly improved the in vitro water absorption, degradability and apatite-formation ability of the m-BG–PLLA composite scaffolds, which were m-BG content dependent. Moreover, addition of the m-BG into PLLA could neutralize the acidic degradation products of PLLA and thus compensate for the decrease of the pH value. In cell culture experiments, the results revealed that the m-BG–PLLA composite scaffolds enhanced attachment, proliferation and alkaline phosphatase (ALP) activity of MC3T3-E1 cells, which were m-BG content dependent. In animal experiments, the SRmCT and histological elevation results showed that the composite scaffolds significantly improved osteogenesis in vivo . It can be suggested that incorporation of bioactive materials of m-BG into PLLA was a useful approach to obtain composite scaffolds with improved properties (such as water absorption, degradability, bioactivity and osteogenesis), and the composite scaffolds with excellent biocompatibility could be promising bioactive implants for bone regeneration.